Electrical Properties of Vertical p‐NiO/n‐Ga2O3 and p‐ZnCo2O4/n‐Ga2O3 pn‐Heterodiodes. Issue 7 (1st March 2019) - Schlupp, Peter; Splith, Daniel; von Wenckstern, Holger; Grundmann, Marius
Abstract : Vertical β ‐Ga2 O3 ‐based pn‐heterostructures are investigated by current–voltage measurements and thermal admittance spectroscopy. The β ‐Ga2 O3 thin films are grown by pulsed laser deposition (PLD) on (00.1)ZnO:Ga/(11.0)Al2 O3 substrates at 670 °C. Two different p‐type oxides are used to fabricate pn‐heterodiodes which are investigated with respect to rectification, temperature stability, and breakdown behavior. For that, p‐NiO and p‐ZnCo2 O4 are grown by PLD at room temperature on top of a β ‐Ga2 O3 thin film, respectively. The rectification ratio at room temperature is about nine orders of magnitude, the ideality factor is about 2 and the on‐resistance is below 1 Ω cm 2 . Both diode types did not show degradation for temperatures up to 100 °C. Thermal admittance spectroscopy revealed defects in β ‐Ga2 O3 with thermal activation energy E a of about 200 meV for both diode types. Additionally, a level with E a ≈ 240 meV is detected for the NiO/Ga2 O3 diodes only. In general, both diode types are suited to realize pn‐heterodiodes with high rectification, but NiO is especially interesting for defect characterization by deep‐level optical spectroscopy due to its transparency up to about 3.7 eV. Abstract : Vertical β ‐Ga2 O3 ‐based pn‐heterostructures are investigated by current–voltage measurements and thermal admittance spectroscopy. As p‐type materials room temperature fabricated NiO or ZnCo2 O4 is used. The vertical device layout is realized using a highly conducting ZnO:Ga back contact layer. High current rectification of nine orders of magnitude is observed. A defect level with an activation energy of about 200 meV is found in the β ‐Ga2 O3 .